ZERO RELATIONAL PROCESS IN LAMPUNG CLAUSE - Afrianto Afrianto (Linguistik Indonesia, 2022)
This research presents a configuration of relational clause which does not have a relational process. Such a process is called zero relational process. However, this non-process relational clause has an alternative process which is called attributive/identifying processor demonstrated by the attribute or identifying processor demonstrated by the value and token. Accordingly, this research argues that both attribute and value are connected to the carrier and the token syntactically and semantically because they function to predicate carrier and token through modifying (attribute) and identifying-representing-defining (value). In other words, an attribute can function as the attribute (modifier) and the process (attributive processor) while a value can function as the value (identifier) and the process (identifying processor). Furthermore, it is found that an attribute can construe the characteristics of a carrier and demonstrate numerical information (number, grade, and quantity). On the other hand, a value provides identity, representation, and definition for the token.